Pityriasis rosea in pregnancy: report of a spousal occurrence and craniosynostosis in the healthy newborn - Tiffany Y. Loh (Mattioli1885, 2016)
Background: Pityriasis rosea is a papulosquamous disease. It may occur during pregnancy; in this setting, it has occasionally been associated with adverse outcomes.